Murder go round - Perry, Carol J. (Perry, Carol J. Witch City mystery, 2017)
Lee Barrett has agreed to attend a storage auction with Aunt Ibby-even though she suspects the forgotten rooms will yield more junk than treasure. Her skepticism vanishes once the two win a bid on an overlooked locker and uncover a trove of beautiful curiosities, including a stunning wooden carousel horse with gentle eyes and fading paint. But just before Lee leaves the fairground relic at a local repair shop, the sight of a silver samovar awakens her psychic abilities and conjures visions of murder.